1978
DOI: 10.1001/jama.1978.03290080056028
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Intermittent Porphyria With Large Doses of Propranolol

Abstract: A patient had an acute attack of intermittent porphyria with severe neurologic manifestations, hypertension, and tachycardia. Treatment with propranolol hydrochloride (Deralin [Israel]; Inderal, comparable US product) intravenously administered in a total dose of 284 mg during a period of 18 hours, was followed by clinical remission associated with a decline in urinary excretion of porphyrin precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In our case, the very high doses and plasma levels used without the occurrence of hypoten sion, bradycardia or heart failure [as reported in 1 case of porphyria (3)] imply an extreme overstimulation of the adrenergic system during the attack. The decrease in the excretion of urinary porphyrins observed in our patient concomi tantly with propranolol administration may be related to its repression of ALA synthetase and is in accordance with previous clinical and experimental reports (6,9,16).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our case, the very high doses and plasma levels used without the occurrence of hypoten sion, bradycardia or heart failure [as reported in 1 case of porphyria (3)] imply an extreme overstimulation of the adrenergic system during the attack. The decrease in the excretion of urinary porphyrins observed in our patient concomi tantly with propranolol administration may be related to its repression of ALA synthetase and is in accordance with previous clinical and experimental reports (6,9,16).…”
Section: Discussionsupporting
confidence: 93%
“…Propranolol has been shown to have benefi cial effects in a few attacks of porphyria variegata (1, 2, 6) and in AIP (9). It has been suggested that the mechanism may be through its partial repression of ALA synthetase induc tion as well as by its effect on membranes (16).…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol (3 × 20 mg/day) is another possibility to treat symptoms of adrenergic hyperactivity in AIP, because it seems to decrease the induction of ALAS (6,15). Since attacks of AIP can be precipitated by hormonal factors, devastating the lives of young women suffering monthly premenstrual porphyric crisis, many treatment regimens were tried.…”
Section: European Journal Of Endocrinology (1999) 141mentioning
confidence: 99%
“…glucose administration (300-500 g/day) and/or the administration of haematin or haem arginate (165 mg/day) (4,5). Propranolol (3 × 20 mg/day) can be used to treat symptoms of adrenergic hyperactivity associated with AIP (6).…”
Section: Introductionmentioning
confidence: 99%
“…propranolol. Propranolol in high doses (284 mg intravenously during a period of 18 hours and after that 300 to 950 mg/day orally) has been reported to effect a clinical remission associated with a decline in urinary excretion of porphyrin precursors in an acute attack of intermittent porphyria (Douer et al 1978).…”
mentioning
confidence: 99%